Dengue: Recent Trends - Rabindran Chandran; D Sharad Gedam (International Journal of Medical Research and Review, 2015)
Today dengue ranks as the most important mosquito-borne viral disease in the world & its incidence has increased 30-fold over the last 50 years. In India there is recent increase in cases of Dengue in last few years.